2021
DOI: 10.3390/su13137301
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and Swell–Shrink Characteristics of Clay and Recycled Zeolite Mixtures for Liner Construction in Sustainable Waste Landfill

Abstract: This paper presents research considering hydraulic as well as swelling and shrinkage characteristics of potential recycled fine particle materials for compacted clay liner for sustainable landfills. Five locally available clay soils mixed with 10% (by mass) of NaP1 recycled zeolite were tested. The performed analysis was based on determined plasticity, cation exchange capacity, coefficient of saturated hydraulic conductivity after compaction, several shrinkage and swelling characteristics as well as, finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The study conducted by Rubinos et al investigated the geotechnical and hydraulic characteristics, advantages, and disadvantages of various waste materials, including paper mill sludge, cement kiln dust, biochar modified clay, and red mud as constituents for landfill barriers. The findings of this study demonstrated that the modified sludge fulfilled the requirements for landfill cover materials in terms of unconfined compressive strength and permeability coefficient tests [20][21][22]. The compaction, screening, and CT scan tests were conducted by Li et al on a renewable construction waste mixture.…”
Section: Introductionmentioning
confidence: 65%
“…The study conducted by Rubinos et al investigated the geotechnical and hydraulic characteristics, advantages, and disadvantages of various waste materials, including paper mill sludge, cement kiln dust, biochar modified clay, and red mud as constituents for landfill barriers. The findings of this study demonstrated that the modified sludge fulfilled the requirements for landfill cover materials in terms of unconfined compressive strength and permeability coefficient tests [20][21][22]. The compaction, screening, and CT scan tests were conducted by Li et al on a renewable construction waste mixture.…”
Section: Introductionmentioning
confidence: 65%
“…According to the Unified Soil Classification System [ 23 ], clinoptilolite was classified as silt with a high liquid limit (MH). In order to explore the influence of clinoptilolite content on soil’s water-holding capacity, and in consideration of the hydraulic conductivity, adsorption performance, gas resistance, and other requirements of CCC, the replacement content of clinoptilolite was set as 0%, 3%, 5%, 10%, and 15% according to the literature [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, some research shows that zeolite did not reduce the desiccation cracking properties of bentonite [43]. And the expansion and shrinkage of zeolite-modi ed clays increase [44]. After three cycles of drying and wetting, the permeability required can not be maintained due to the enhanced cracking properties [44].…”
Section: Introductionmentioning
confidence: 98%
“…And the expansion and shrinkage of zeolite-modi ed clays increase [44]. After three cycles of drying and wetting, the permeability required can not be maintained due to the enhanced cracking properties [44]. Sodium polyacrylate(Na-PAA) has better water absorption and retention properties than zeolite [36].…”
Section: Introductionmentioning
confidence: 99%